Obtaining and Characterization of a Polydisperse System Used as a Transmembrane Carrier for Isosorbide Derivatives - Borcan, Florin; Len, Adél; Bordejevic, Diana A.; Dudás, Zoltán; Tomescu, Mirela C.; Valeanu, Adina N. (Frontiers in Chemistry, 2020)
Due to their effect of vasodilatation, isosorbide nitrates represent one of the most important and most used solution for angina pectoris. Unfortunately, these compounds have multiple dose-related adverse drug reactions such as headache, weakness, mild dizziness, and occasionally heart rate changes, nausea, vomiting, and sweating. The main aims of this research were to obtain and to evaluate new polyurethane structures which can be used as a proper transmembrane carrier with an improved release kinetic. Chitosan-based PU structures were obtained by a polyaddition process between hexamethylene diisocyanate and a mixture of chitosan, butanediol and polyethylene glycol in the presence of caffeine as a synthesis catalyst. The obtained samples (with and without active substances) were characterized regarding the encapsulation and release rate (UV-Vis spectra), chemical composition (FT-IR), thermal stability (thermal analysis), morphology changes (SEM and SANS) and in vivo irritation tests. These methods revealed no significant differences between the two sample structures. Multipopulational structures with sizes between 73 and 310 nm, with an increased tendency to form clusters and a high resistance to heat (up to 280 °C) were obtained. This study presents an alternative administration of isosorbide derivatives based on a polyurethane carrier with a high biocompatibility and a prolonged release.